Microalgal bioactives as emerging nutritional regulators of apoptosis and neuroplasticity: targeting metabolic dysfunction in aging, neurodegenerative diseases, and cancer - Wang, Aili; Bai, FenTao; Hua, Jing (Frontiers in Pharmacology, 2025)
Microalgae are a rich source of multifunctional bioactive metabolites, such as carotenoids, polyunsaturated fatty acids, phycobiliproteins, and phenolics, that influence cellular metabolism, redox balance, and gene expression. Evidence from in vitro, in vivo, and limited clinical studies shows their dual capacity to support neuronal survival and plasticity while inducing apoptosis in cancer cells. In neurodegenerative diseases, these metabolites improve mitochondrial function, reduce neuroinflammation, enhance neurotrophic factor expression, and promote synaptic remodeling. In cancer, they trigger cell-cycle arrest, inhibit angiogenesis and metastasis, and activate both intrinsic and extrinsic apoptotic pathways. Literature for this review was identified through structured searches in PubMed, Scopus, Web of Science, and Google Scholar (2000–2025) using predefined keywords, with inclusion limited to peer-reviewed English studies on microalgal metabolites and apoptosis or neuroprotection. This review critically examines mechanistic, translational, and safety evidence, highlighting both therapeutic promise and current limitations, and proposes microalgae-derived metabolites as potential dual-action modulators for oncology and neurology.